"Economic liberalization in India: analytics, experience and lessions" - Nayyar, Deepak (New Delhi, 1996)
The aim of this essay, based on my lectures, is to provide an analysis and an assessment of the economic liberalization in India based on theory and experience. The choice of the theme was shaped, in part, by the reality in the national context and the conjuncture in the international context. The significance of the subject, however, extends beyond the reality and the conjuncture. The process of liberalization may affect the living conditions of millions of people. What is more, this attempt at transformation of the economy may have profound implications for polity and society. It is not surprising, then, that there is an intense debate on and a widespread interest in the subject. It is hoped that this essay would stimulate informed debate and contribute to understanding among a much wider readership of concerned citizens.
Keywords: Liberalization